2021
DOI: 10.1183/13993003.00929-2021
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pneumothorax in the UK: a prospective observational study using the ISARIC WHO clinical characterisation protocol

Abstract: Pneumothorax is an important complication of COVID-19 [1, 2]. Based on a series of 60 individuals, we previously estimated that 0.91% of people admitted to hospital with COVID-19 develop pneumothorax [1]. Males accounted for three quarters of those affected, and patients requiring non-invasive or invasive ventilatory support appeared at elevated risk. In a separate series of ventilated patients with COVID-19, barotrauma, defined as pneumothorax or pneumomediastinum, was found to be an independent risk for deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 11 publications
4
37
3
Order By: Relevance
“…As a demonstration of the impact of these complications of COVID-19, numerous studies have been published on this topic since the pandemic outbreak, but only nine included a large number of patients, and only two included a control group (4). The results of a recently published study considering more than 130,000 hospitalized COVID-19 patients in the United Kingdom (8) are in line with the present study. However, there are some differences with previous works that have to be highlighted.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As a demonstration of the impact of these complications of COVID-19, numerous studies have been published on this topic since the pandemic outbreak, but only nine included a large number of patients, and only two included a control group (4). The results of a recently published study considering more than 130,000 hospitalized COVID-19 patients in the United Kingdom (8) are in line with the present study. However, there are some differences with previous works that have to be highlighted.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in our study, these results have been shown to be independent of age, sex, and the severity of the disease based on the P/F ratio and the need for respiratory support. Many studies reported similar results in both invasively and non-invasively ventilated patients [7,8,10,14], although not all studies assessed…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations